2004
DOI: 10.1002/elan.200302935
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Tubular Sensor Based on a Polypyrrole‐Doped Membrane for the Potentiometric Determination of the Dodecylsulfate Anion in a FIA System

Abstract: Potentiostatic polymerization of polypyrrole doped with dodecylsulfate anion (DS À ) was carried out in situ over a tubular composite (graphite-epoxy resin) support in order to develop a potentiometric DS À sensor (TISE) suitable for flow injection analysis (FIA). The sensibility of the TISE was maximized using the SIMPLEX algorithm in terms of the concentration of the pyrrole monomer, the concentration of DS À , the potential imposed and polymerization time. Response times between 2 and 4 minutes were observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…The analytical performance of PPy/DS is comparable to that of plasticized PVC-based ISEs for DS À [108]. A very simple procedure for manufacturing of a solidstate NO 3 À -ISE by electrosynthesis of PPy doped with NO 3 À on a pencil lead was described by Bendikov and Harmon [109].…”
Section: CLmentioning
confidence: 95%
See 1 more Smart Citation
“…The analytical performance of PPy/DS is comparable to that of plasticized PVC-based ISEs for DS À [108]. A very simple procedure for manufacturing of a solidstate NO 3 À -ISE by electrosynthesis of PPy doped with NO 3 À on a pencil lead was described by Bendikov and Harmon [109].…”
Section: CLmentioning
confidence: 95%
“…Ramírez-Silva et al [108] used electrochemically synthesized PPy doped with dodecylsulfate (PPy/DS) for the development of a tubular solid-state ISE for determination of DS À in a flow injection analysis system. The analytical performance of PPy/DS is comparable to that of plasticized PVC-based ISEs for DS À [108].…”
Section: CLmentioning
confidence: 99%
“…Potentiometric method of dodecylsulfate anions determination has been proposed [174], with detection limit 2 Â 10 À6 M. Amperometric methods of surfactants ion determination are characterized by a lower detection limit. The accessible concentration range is 10 À7 -10 À2 M, based on measuring the current decrease caused by ion exchange inhibition [173].…”
Section: Interactions With Surfactantsmentioning
confidence: 99%
“…Electrochemical formation of conducting polymers films has attracted considerable attention due to the wide range of possible applications of these materials in electrocatalysts and chemical sensors [1][2][3][4][5][6]. They are used in computer screens to baffle radiations, for displays in cellular phones and notebooks screens, to maintain the electric charge in batteries, to fabricate completely organic and biodegradable batteries, as part of light emitting diodes (LED's) as well as chemical sensors for sewage and atmospheric gases, showing a favorable performance.…”
Section: Introductionmentioning
confidence: 99%
“…However, other aspects have been less studied, such as the hydrodynamic conditions of the system. Traditionally, electropolymerization of the polypyrrole (Ppy) has been studied using electrodes based on noble metals such as gold or platinum, but other authors have reported electropolymerization on aluminium [14], copper [15], stainless steel [7,16], carbon paste electrode [5,6] and vitreous carbon [7,9]. Nevertheless, there are still numerous fundamental aspects to be studied in the formation of Ppy during its initial stages, however, the kinetics and mechanisms of formation stand out as highly relevant for they refer to fundamentals, which are likely to be found during its electropolymerization.…”
Section: Introductionmentioning
confidence: 99%